2021
DOI: 10.3390/ijms22136964
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Transient Hyperglycemia Induces Changes in the Expression Patterns of IL6 and ADIPOQ Genes and Their Associated Epigenetic Modifications in Differentiating Human Visceral Adipocytes

Abstract: Adipokines secreted by hypertrophic visceral adipose tissue (VAT) instigate low-grade inflammation, followed by hyperglycemia (HG)-related metabolic disorders. The latter may develop with the participation of epigenetic modifications. Our aim was to assess how HG influences selected epigenetic modifications and the expression of interleukin 6 (IL-6) and adiponectin (APN; gene symbol ADIPOQ) during the adipogenesis of human visceral preadipocytes (HPA-v). Adipocytes (Ads) were chronically or transiently HG-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Visceral adipose tissue plays an important role in the development of T2DM, as well as NAFLD, by producing cytokines and activating the NF-κB pathway [226,227]. Increased gluconeogenesis and attenuation of insulin sensitivity are observed due to the activity of protein kinase Cε, fetuin A/B, retinol-binding protein 4, or selenoprotein P. T2DM patients typically demonstrate higher hepatic fat content and inflammation.…”
Section: T2dmmentioning
confidence: 99%
“…Visceral adipose tissue plays an important role in the development of T2DM, as well as NAFLD, by producing cytokines and activating the NF-κB pathway [226,227]. Increased gluconeogenesis and attenuation of insulin sensitivity are observed due to the activity of protein kinase Cε, fetuin A/B, retinol-binding protein 4, or selenoprotein P. T2DM patients typically demonstrate higher hepatic fat content and inflammation.…”
Section: T2dmmentioning
confidence: 99%
“…H3K4me3 enhancement was observed in proinflammatory genes ( MCP-1 and TNF- α), profibrotic genes ( TGF-β1 and collagen III ), and histone-modifying enzyme ( SET1 and BRG1 ) in an ischemia-reperfusion injury animal model ( Naito et al, 2009 ). In IR state, H3K4me3 and H3K9/14ac were reduced in adipose tissue ( Figure 2 ) ( Wróblewski et al, 2021 ). The enhancement of the H3K4me3 level promoted PEPCK expression, which might contribute to hyperglycemia and anorexia in mandarin fish fed on carbohydrate-rich diets ( You et al, 2020 ).…”
Section: Histone Methylation In Type 2 Diabetesmentioning
confidence: 99%
“…IRS binds to the kinase regulatory subunit of PI3K (PI3K-R), the central molecule of the pathway. This, in turn, causes activation of the catalytic PI3K (PI3K-C) subunit that converts phosphatidylinositol (4,5)-biphosphate (PIP2) to phosphatidylinositol (3,4,5)-triphosphate (PIP3) [8]. The main insulin pathway regulator, PTEN, (phosphatase and tensin homolog), inhibits further signal transduction by PIP3 dephosphorylation [10].…”
Section: Introductionmentioning
confidence: 99%
“…VAT surrounds the abdominal viscera in the mesentery and omentum. It produces and releases a large number of adipocytokines that influence both VAT and other tissues [ 2 , 3 ]. It is suggested that hyperglycemia (HG), a typical marker of diabetes causing nutrient stress, may alter the production of adipocytokines and change biochemical pathways including insulin signaling [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation